Information and the right to information in commercial companies – new and old issues in the age of information technologies (De Legibus - Law Journal, 2025)
The present article aims to analyse certain issues related to the exercise of the right to information in commercial companies and the impact that the emergence of new technologies has had and may come to have in this context. Our research will first focus on the legal framework provided in the Portuguese Commercial Companies Code for Private Limited Companies (Sociedades por Quotas) and Joint-Stock Companies (Sociedades Anónimas) with respect to the right to information. Additionally, we will briefly address the matter of information within the scope of the capital markets. Finally, we will discuss some of the new technologies that have expanded and facilitated access to information in this area, while also considering the risks and challenges that may arise in this regard.
Keywords: Right to Information; Commercial Companies; Capital Markets; Information Technology